2015
DOI: 10.1073/pnas.1504025112
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional model of surfactant replacement therapy

Abstract: Surfactant replacement therapy (SRT) involves instillation of a liquid-surfactant mixture directly into the lung airway tree. It is widely successful for treating surfactant deficiency in premature neonates who develop neonatal respiratory distress syndrome (NRDS). However, when applied to adults with acute respiratory distress syndrome (ARDS), early successes were followed by failures. This unexpected and puzzling situation is a vexing issue in the pulmonary community. A pressing question is whether the insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 35 publications
1
99
0
Order By: Relevance
“…We observed that the presence of a transverse gravitational field induces asymmetries in plug splitting, which are mitigated by an increase in the driving gas flow rate. This is in agreement with previous experimental and analytical models introduced by Zheng et al (2005) and Filoche et al (2015). We measured the asymmetry of the splitting using the splitting ratio, R S , and generated sufficient numerical data to allow for a nonlinear least-squares fit to that could be used to predict an approximate splitting ratio for a given roll angle and capillary number.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We observed that the presence of a transverse gravitational field induces asymmetries in plug splitting, which are mitigated by an increase in the driving gas flow rate. This is in agreement with previous experimental and analytical models introduced by Zheng et al (2005) and Filoche et al (2015). We measured the asymmetry of the splitting using the splitting ratio, R S , and generated sufficient numerical data to allow for a nonlinear least-squares fit to that could be used to predict an approximate splitting ratio for a given roll angle and capillary number.…”
Section: Resultssupporting
confidence: 87%
“…Note that the experimental and theoretical results from Zheng et al (2005) are for dry walls in the daughters and the two-dimensional model presented here and the one-dimensional model in Filoche et al (2015) have wet walls in the daughters. Since the Bond number used to generate the results presented in figure 5 and table 1, and the nonlinear fitting is Bo = 2.5 and the Bond number used in the dataset from Zheng et al (2005) is Bo = 1.26, we must adjust the roll angle before we can compare results.…”
Section: Two-dimensional Airway Bifurcation Modelmentioning
confidence: 71%
See 3 more Smart Citations